Performance and methane emissions in dairy cows fed oregano and green tea extracts as feed additives - Kolling, G. J.; Stivanin, S. C. B.; Gabbi, A. M.; Machado, F. S.; Ferreira, A. L.; Campos, M. M.; Tomich, T. R.; Cunha, C. S.; Dill, S. W.; Pereira, L. G. R.; Fischer, V. (Journal of Dairy Science, 2018)
Plant extracts have been proposed as substitutes for chemical feed additives due to their potential as rumen fermentation modifiers and because of their antimicrobial and antioxidant activities, possibly reducing methane emissions. This study aimed to evaluate the use of oregano (OR), green tea extracts (GT), and their association as feed additives on the performance and methane emissions from dairy between 28 and 87 d of lactation. Thirty-two lactating dairy cows, blocked into 2 genetic groups: 16 Holstein cows and 16 crossbred Holstein-Gir, with 522.6 ± 58.3 kg of body weight, 57.2 ± 20.9 d in lactation, producing 27.5 ± 5.0 kg/cow of milk and with 3.1 ± 1.8 lactations were evaluated (means ± standard error of the means). Cows were allocated into 4 treatments: control (CON), without plant extracts in the diet; oregano extract (OR), with the addition of 0.056% of oregano extract in the dry matter (DM) of the diet; green tea (GT), with the addition of 0.028% of green tea extract in the DM of the diet; and mixture, with the addition of 0.056% oregano extract and 0.028% green tea extract in the DM of the diet. The forage-to-concentrate ratio was 60:40. Forage was composed of corn silage (94%) and Tifton hay (6%); concentrate was based on ground corn and soybean meal. Plant extracts were supplied as powder, which was previously added and homogenized into 1 kg of concentrate in natural matter, top-dressed onto the total mixed diet. No treatment by day interaction was observed for any of the evaluated variables, but some block by treatment interactions were significant. In Holstein cows, the mixture treatment decreased gross energy and tended to decrease the total-tract apparent digestibility coefficient for crude protein and total digestible nutrients when compared with OR. During the gas measurement period, GT and OR increased the digestible fraction of the ingested DM and decreased CH4 expressed in grams per kilogram of digestible DMI compared with CON. The use of extracts did not change rumen pH, total volatile fatty acid concentration, milk yield, or most milk traits. Compared with CON, oregano addition decreased fat concentration in milk. The use of plant extracts altered some milk fatty acids but did not change milk fatty acids grouped according to chain length (short or long), saturation (unsaturated or saturated), total conjugated linoleic acids, and n-3 and n-6 contents. Green tea and oregano fed separately reduced gas emission in cows during the first third of lactation and have potential to be used as feed additives for dairy cows.
Keywords: Catechin; Essential oil; Methane emission; Milk composition